Effect of molecular weight on the properties of polyethylene glycol doped by multiwalled carbon nanotubes - Bulavin, L. A.; Melnyk, I. A.; Goncharuk, A. I.; Klepko, V. V.; Lebovka, N. I.; Lysenkov, E. A. (Reports of the National Academy of Sciences of Ukraine, 2015)
The differential scanning calorimetry and electrical conductivity methods are used to study the influence of doping multiwalled carbon nanotubes (NTs) on the properties of polyethylene glycol (PEG) of different molecular weights, Mw (PEG-400, PEG-1000, PEG-10000). Dependences of the degree of crystallinity of polymers and the temperature behavior of conductivity on the concentration of NTs are researched. The obtained data indicate a strong influence of the molecular weight of PEG on the spatial distribution of NTs and the electrical conductivity of researched systems.